2009
DOI: 10.1002/pola.23337
|View full text |Cite
|
Sign up to set email alerts
|

High Tg and high organosolubility of novel unsymmetric polyimides

Abstract: A series of new polyimides (PIs) containing di-tert-butyl side groups were synthesized via a polycondensation of 1-(4-aminophenoxy)-4-(4-amino-2-methylphenyl)-2,6-di-tert-butylbenzene (3) with various aromatic tetracarboxylic dianhydrides. The novel unsymmetric PIs exhibited a low dielectric constants (2.78-3.02), low moisture absorption (0.53-1.35%), excellent solubility, and high glass transition temperature (308-450 C). The PI derived from the new diamine and the very rigid naphthalene-1,4,5,8-tetracarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Recently, Ueda reported a soluble poly(binaphthylene ether) with the values of 2.70 at 20 GHz by a simple oxidative coupling polymerization [9]. Chern reported a series of polyimides containing di-tert-butyl pendant groups via a one-step polycondensation [10]. These polyimides had good solubility at the tested solvents and their films exhibited low dielectric constants with the values of 2.78-3.02 at 1 MHz.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Ueda reported a soluble poly(binaphthylene ether) with the values of 2.70 at 20 GHz by a simple oxidative coupling polymerization [9]. Chern reported a series of polyimides containing di-tert-butyl pendant groups via a one-step polycondensation [10]. These polyimides had good solubility at the tested solvents and their films exhibited low dielectric constants with the values of 2.78-3.02 at 1 MHz.…”
Section: Introductionmentioning
confidence: 97%
“…These aromatic polymers with k of 3.1-3.9 at 1 MHz are often insoluble and infusible due to their rigid chain characteristics, which lead to processing difficulties and hinder their application in industries. To overcome these problems, one of the effective strategies is introduction of bulky pendant groups along the polymer backbone, which can reduce chain packing and density, and finally improve the solubility and dielectric properties of the resulting aromatic polymers [4,9,10]. Recently, Ueda reported a soluble poly(binaphthylene ether) with the values of 2.70 at 20 GHz by a simple oxidative coupling polymerization [9].…”
Section: Introductionmentioning
confidence: 97%
“…These PETI-series exhibited favorable melt stabilities of no more than 10 Pa·s at 280 C for 2 h, their cured T g s also increased gradually from 298 C to 375 C. It was found that the low melt viscosity could be improved greatly by introducing bulky rigid substituents like 2,3,3,4-biphenyltetracarboxcylic anhydride (-BPDA) into the backbone without deteriorating its thermal stability [17] . Recently, Ishida et al have developed highly soluble polyimide resins by introducing 4,4'-(9-fluorenylidene) dianiline (BAFL) groups into the backbones of TriA-PI which was prepared from -BPDA, 4,4-diaminodiphenyl ether (4,4-ODA) and 4-phenylethynylphthalic anhydride (4-PEPA).…”
Section: Introductionmentioning
confidence: 97%
“…Many attempts have been made to improve the processability of PIs without sacrificing their thermal and mechanical properties. During the past decades, some progress has been made in the chemical modification of the parent PIs structure to get more soluble polymer derivatives, for example, introducing the flexible linkages or geometrically asymmetric units, bulky lateral groups or noncoplanar structures into the polymer backbone [8][9][10][11][12][13][14][15]. It also has been demonstrated that incorporation of a cyclic side cardo group, such as a fluorene, a phenylcyclohexane, or an adamantane group, into the macromolecular backbone was quite effective to improve the solubility of PIs without deteriorating their inherent excellent properties [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%